TEACHER POWER BASES AS PERCEIVED BY SECONDARY (HIGH) SCHOOL STUDENTS: A FIELD STUDY AT JERASH CITY, JORDAN - Hawamdeh, Basem Ali (European Scientific Journal, ESJ, 2013)
The study aims to identify teacher power bases as perceived by Secondary (High) School students, it also aims to discern the types of power or authority students prefer and the causes thereof. In order to achieve the objectives of the study, the researchers opted for the organized interview method; the selected sample included 85 male and female students. The findings show that teacher power bases are listed in the following descending order as perceived by students: referent, expertise, power/strength and legitimacy. Based on the interviews conducted as new base or power emerged that pertains to attitude/ behavior and hence called â€œattitudinal/behavioralâ€.